PENGAWASAN PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR PROVINSI KALIMANTAN TENGAH TAHUN 2020 DALAM PERSPEKTIF KEADILAN BERMARTABAT (Jurnal Huma Betang Demokrasi, 2021)
Justice is one of the principles in local elections. The principle of justice is that all citizen has the right to vote and be elected as well be treated equally. The principle of justice is the just attitude of election organizers in relation to the plurality of society and the very high political interests of various parties. The credibility and integrity of individual election organizers is an important (key) issue, equal and congruent with the Dignified Election of a society and a nation. The implementation of the 2020 Central Kalimantan Governor and Deputy Governor Elections can run safely, smoothly and conducively, not apart from the role of the Provincial Bawaslu of Central Kalimantan, namely conducting supervision in every stage of the election, by taking preventive and repressive measures. In doing efforts of preventive and repressive measures, the Bawaslu of Central Kalimantan realizes justice, for the make of a just democracy and dignified Local Elections.